PENGARUH LATIHAN BARBELL PULLOVER TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA TIM VOLI PUTRA SMP NEGERI 6 PEKANBARU - Amat Nordin; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, the purpose of this research is want to know is there the effect of Barbell Pullover exercise toward strenght of arm and shoulder musclus of smpn 6 pekanbaru man vollyball club, so when do under servise, the ball can pass over the net. Type of this research is experimental, the population in this research was the students of smpn 6 pekanbaru man vollyball club who actively doing exercise, the total was 10 students. Sampling technique used as sample ( sugiyono 2008 : 124 ). Total sample of this research is 10 students of smpn 6 pekanbaru man vollyball club. Data tecnique used was surfaited sampling, it is determination of the sample when all members are the population are used as sample. The instruments was used in this research was expanding dynamometer, which is aimed to measure the strength og arm and shoulder muscles. After that, the data was analysis by using statistic to examine the normality with liliefors test on the significant level 0,05a. The subritted hypothesis was there is the effect of Barbell Pullover exercise toward strength of arm and shoulder muscles. Based on the data analysis t test showed T count was 21,95 and T table was 1,812, it means that T count > T table. Based on the statistic data analysis, the average of preetest was 12,1 and the average of posttest 15,7 was it. Shows that the data was normal. In conclution , there was the effect of Barbell Pullover exercise toward strength of arm and shoulder of smpn 6 pekanbaru man vollyball club.Keywords : Barbell Pullover, Strenght of arm and muscles.